Artemisinin and its derivatives in treating protozoan infections beyond malaria - Loo, Cecilia Shi Ni (Pharmacol Res, 2016)
Many parasitic protozoan diseases continue to rank among the world’s greatest global health problems, which are also common among poor populations. Currently available drugs for treatment present drawbacks, urging the need for more effective, safer, and cheaper drugs. Artemisinin (ART) and its derivatives are some of the most important classes of antimalarial agents originally derived from Artemisia annua L. However, besides the outstanding antimalarial and antischistosomal activities, ART and its derivatives also possess activities against other parasitic protozoa. In this paper, we reviewed the activities of ART and its derivatives against protozoan parasites in in vitro and in vivo, including Leishmania spp., Trypanosoma spp., Toxoplasma gondii, Neospora caninum, Eimeria tenella, Acanthamoeba castellanii, Naegleria fowleri, Cryptosporidium parvum, Giardia lamblia, and Babesia spp. We concluded that ART and its derivatives may be good alternatives for treating other non-malarial protozoan infections in developing countries, although more studies are necessary before they can be applied clinically.